2020
DOI: 10.3390/ph13110360
|View full text |Cite
|
Sign up to set email alerts
|

Gene Regulation Using Spherical Nucleic Acids to Treat Skin Disorders

Abstract: Spherical nucleic acids (SNAs) are nanostructures consisting of nucleic acids in a spherical configuration, often around a nanoparticle core. SNAs are advantageous as gene-regulating agents compared to conventional gene therapy owing to their low toxicity, enhanced stability, uptake by virtually any cell, and ability to penetrate the epidermal barrier. In this review we: (i) describe the production, structure and properties of SNAs; (ii) detail the mechanism of SNA uptake in keratinocytes, regulated by scaveng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 91 publications
0
16
0
Order By: Relevance
“…Completed trials have shown no serious adverse events, mild injection site reactions and flu‐like symptoms, dose‐related systemic immune activation, and more diverse tumor cell infiltration with AST‐008 injection compared to noninjected tumors. [ 95 ] As such, additional immunostimulatory SNAs consisting of RNAs selective for TLR‐7/8 were synthesized and characterized. [ 50 ]…”
Section: Snas For Disease Diagnosis and Treatmentmentioning
confidence: 99%
See 3 more Smart Citations
“…Completed trials have shown no serious adverse events, mild injection site reactions and flu‐like symptoms, dose‐related systemic immune activation, and more diverse tumor cell infiltration with AST‐008 injection compared to noninjected tumors. [ 95 ] As such, additional immunostimulatory SNAs consisting of RNAs selective for TLR‐7/8 were synthesized and characterized. [ 50 ]…”
Section: Snas For Disease Diagnosis and Treatmentmentioning
confidence: 99%
“…Rosi et al first demonstrated that SNAs could enter cells and regulate gene expression using single-stranded DNA. [ 94 , 95 ] Since then, double-stranded DNA, siRNA, or miRNA conjugates have been applied to SNAs. [ 92 , 96 98 ] The aggregation of surface oligonucleotides will determine SNA’s biological behaviors from the moment they interact with cells in vitro or organs in vivo.…”
Section: Organizing Surface Dna Aggregationmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, LSNAs prepared from oligonucleotide-phospholipid conjugates have been shown to possess high serum stability and display higher cell uptake as compared to LSNAs synthesized using cholesterol terminated (anchoring) oligonucleotides . Moreover, these structures are medically relevant and thus far have been the basis for 6 clinical trials. …”
mentioning
confidence: 99%